Розробка безпроводової мережи із застосуванням технології LoRa - Матеко, А. О.; Шостко, І. С. (ХНУРЕ, 2025)
This work is discusses wireless network technology LoRa. LoRa (Long Range) is a wireless communication technology designed for long-distance data transmission with low power consumption. It employs spread-spectrum modulation to enhance signal resilience against interference, making it an ideal choice for IoT applications. LoRa networks, operating in unlicensed ISM bands, provide cost-effective solutions for smart cities, industrial monitoring, and agricultural automation. LoRaWAN, an open standard protocol, enables scalable deployment of IoT networks by managing communication between end devices and gateways. The technology’s key advantage lies in its ability to maintain reliable data transmission over several kilometers while ensuring minimal energy consumption.
Keywords: LoRa; Long Range